POST-INDUSTRIAL ELEMENTS IN URBAN DEVELOPMENT OF LOS ANGELES (XX – EARLY XXI CENTURY) (World Science, 2018)
The article is dedicated to the distinction of specific features of urban development of Los Angeles, which can serve as an example of the emergence of a new urban paradigm of post-industrial nature.